The new record of Philodina gregaria from Sôya Coast and life history of the species - Wada, Tomotake; Kudoh, Sakae (2019)
The Tenth Symposium on Polar Science/Ordinary sessions : [OB] Polar Biology, Wed. 4 Dec. / Entrance Hall (1st floor) , National Institute of Polar Research conference object